Program Pembinaan Karakter dan Kepemimpinan Siswa berbasis Nilai-Nilai Budaya Lokal bagi Generasi Muda di Papua - Rif’iy Qomarrullah; Fredrik Sokoy; Ewendi W. Mangolo; Lestari Wulandari S; Zainal Widyanto; Efraim Elfan Andi Bonga; Jenita Ralahalu; Yoel Solossa (Institut Nalanda, 2026)
The declining appreciation of character values and leadership among young generations has become a significant educational challenge amid globalization and the rapid development of digital technology. These changes have influenced students’ attitudes, social interactions, and awareness of cultural values, making character strengthening increasingly important. This community service program focused on developing students’ character and leadership through the integration of Papuan local cultural values among students of SMA YPPK Asisi Sentani and SMP Negeri 2 Jayapura. The activity aimed to strengthen character, leadership skills, and cultural awareness by promoting values such as togetherness, responsibility, discipline, mutual respect, and appreciation of local wisdom. The program was implemented through educational and participatory methods, including training sessions, group discussions, leadership simulations, and reflective learning activities. Students were encouraged to actively engage in collaborative activities that fostered critical thinking, communication skills, teamwork, and leadership attitudes. The results showed improvements in students’ understanding of character values, leadership concepts, teamwork, communication abilities, and awareness of local culture as a foundation for leadership development. Participants also demonstrated greater confidence and responsibility in carrying out group tasks and social interactions. These findings indicate that character and leadership education based on local cultural values can serve as an effective strategy for shaping responsible, adaptive, and value-driven Papuan youth while simultaneously preserving cultural identity in the face of social change.